Thyroid dose assessments due to inhalation of 131I for nuclear medicine workers - Gang Liu; Ye Li; HanYu Zhang; Xue Zhang; Yin Yin Liu; Xiao Qin Wu; Li Mei Niu; Rong Zhang (Frontiers Media S.A., 2022)
BackgroundIn general, medical staff who work in nuclear medicine should be entirely safe in their professional environment. Nevertheless, we already know that the working environment of the nuclear medicine staff is not completely safe due to the handling of high amounts of radionuclides for diagnostic and therapy applications, which is especially relevant for 131I (as a non-sealed source).PurposeThe goal of this study was to assess the inhaled 131I thyroid dose in nuclear medicine workers and to introduce a simple method for internal exposure monitoring.MethodsUsing 2-IN*2-in NaI (Tl) scintillation spectrometer and its supporting software (InSpector Maintenance Utility and Genie 2000), from 2019 to 2021, internal thyroid irradiation monitoring, an internal thyroid irradiation monitoring investi A NaI (Tl) scintillation spectrometer and its sugation was carried out for 3 consecutive years, between 2019 and 2021, in staff members of nuclear medicine departments engaged with iodine therapy.Results131I activity was found highest in the thyroid of nuclear medicine workers involved with the manual packaging and delivery of the radioisotope, while it was not detected in staff members involved with the automatic packaging and drug delivery. The activity range was found to be 30.00 ± 6.60-6070.00 ± 1335.40 Bq for the exposed personnel, and the estimated dose was 0.05-6.77 mSv. In 2021, three workers had an annual equivalent dose above 5 mSv.ConclusionBy monitoring the thyroid 131I in staff members of the nuclear medicine department, it was found that there are 131I internal occupational exposure risks. The best solution is automatic packaging and drug delivery.